The global warming survival handbook 77 essential skills to stop climate change--or live through it - Rothschild, David de; Reiner, Rob; Wall, Kevin; Van Roden, William; Bright, Adam M.; Dickstein, Max; Halpin, Mikki; Gould, Kira; Lewis, Shelley; Naparstek, Aaron; Ness, Eric; Postman, Andrew; et al. (New York Melcher Media, 2007)
Describes ways to prevent global warming, including screwing in the right light bulb, choosing the right grocery bag, and eating vegetables, and includes ten humorous ways to survive on an overheated planet, including buying a camel.
Climate Control: an introduction to global warming -- 10 easy steps to help fight global warming -- How to read this book -- The 77 skills -- If all else fails.
"Official companion to the Live Earth concerts."--Cover.
Keywords: Global warming; Climatic changes